How important are health and education in boosting sub-national economic growth? - Verazulianti Verazulianti; Taufiq Carnegie Dawood; Teuku Zulham (Publisher of Widyagama University of Malang (UWG Press), 2021)
Development of the global economy is marked by increasing attention towards the health sector due to Covid-19 outbreak. This research contributes by examining how important is health and education for provincial economic growth, and connect it with foreign direct investments, and infrastructure spending. Taking Indonesia as a case study, and employing GMM and Fixed Effects methods, the analysis found that improving health and education outcomes are key for sub-national economic growth. However, foreign direct investment, domestic direct investment and public spending on infrastructure failed to support growth in the sub-national level. The finding is robust against alternative specifications. For policy suggestions, in order to dampen the negative economic effects of Covid-19 and to boost growth at post-pandemic period, government at all levels must maintain or even increase public spending in health and education which directly target improvements of health and educational outcomes. To ensure the improvements, public spending must be directed to provide good quality health and educational services; services which enhance health outcomes and develop students’ cognitive skills. In addition, good quality health and educational services must be evenly distributed across sub-nationalities. This is aligned with achieving the UN Sustainable Development Goals number 10; reducing inequality within a country.JEL Classification H51; H52; O15